A lifetime model for creep-fatigue interaction with applications to the creep resistant steel P92. (September 2021) - Riedel, Hermann; Maier, Gerhard; Oesterlin, Heiner
Highlights: A creep-fatigue model based on fatigue microcracks and grain boundary creep damage. New creep-fatigue damage parameter DFC . The model is validated by tests on the steel P92. Better understanding of the creep-fatigue interaction diagram. Improvement of codes and standards. Abstract: Methods proposed by current codes and standards to deal with creep-fatigue problems are far from being satisfactory. For a better understanding, a model is developed based on grain boundary cavitation (representing creep damage) and microcrack growth (representing low-cycle fatigue damage). Creep-fatigue interactions occur by (1) contributions of creep deformation to fatigue crack growth, and (2) enhanced creep rates after load variations, as they occur, e.g., during start/stop cycles. Experiments on the steel P92 confirm the predicted lifetimes as a function of the stress-temperature loading history. A creep-fatigue damage parameter, DFC, is introduced to characterize the load cycle.